Treatment of bipolar depression: clinical practice vs. adherence to guidelines—data from a Bavarian drug surveillance project - Kriner, Paul; Brieger, Peter; Pogarell, Oliver; Schüle, Cornelius; Mußmann, Lisa; Korbmacher, Julie; Seemüller, Florian (Frontiers in Psychiatry, 2024)
Pharmacotherapy of bipolar depression (BPD) is confronted with major clinical challenges, like limited evidence-based treatment options, regular cases of treatment resistance and risk of treatment emergent affective switches. Medical guidelines can support practitioners to make decisions based on current scientific evidence. The objective of this study is to evaluate to what extent recommendations of the 2019 German S3 guidelines "Diagnosis and Treatment of Bipolar Disorders" are reflected in clinical practice in inpatient treatment.We conducted a descriptive analysis of prescription numbers in 2,627 patients with BPD in a naturalistic inpatient setting, analyzing data from the ongoing Bavarian multicenter drug safety project Pharmaco-Epidemiology and Vigilance (Pharmako-EpiVig) from the years 2014-2022.38% of patients were not administered any drug explicitly recommended for treatment of BPD, that is quetiapine, lamotrigine, carbamazepine or olanzapine. Only 6% of patients received monotherapy with one of those drugs. 34% of patients were administered ≥ 4 psychotropic drugs simultaneously.Patients received 912 different therapy regimens of mono-or combination-therapy with mood stabilizers (MS), atypical antipsychotics (AAP) and antidepressants. 72% of patients received an antidepressant, 6% without concomitant prescription of an AAP or MS. Prescription rates of venlafaxine (21% to 14%) and tricyclic antidepressants (9% to 6%) decreased significantly from the first (2014 -2016) to the last (2020 -2022) observed time period. 60% of patients received a MS.Prescription rate of valproate (22% to 14%) decreased significantly, while lithium prescription increased significantly (29% to 35%). 71% of patients were administered an AAP. Quetiapine was the most prescribed drug overall (43%). Only two patients were administered the combination of olanzapine and fluoxetine.Our results demonstrate a substantial gap between guideline recommendations and current clinical practice. The remarkable heterogeneity in treatment regimens, with no discernible dominant treatment approach, is in part a reflection of the complexity of bipolar disorder but also substantiates the need of comprehensive recommendations regarding combination therapies.. Increase in lithium prescription is an encouraging development due to its unique efficacy in maintenance treatment. To improve the quality of clinical practice guideline implementation, more randomized controlled trials should be conducted in the future to prospectively investigate different implementation strategies.